Nanoscaled biphasic calcium phosphate modulates osteogenesis and attenuates LPS-induced inflammation - Su, Yi-Chun; Phan, Trinh T. T.; Wang, Tzu-Wei; Chang, Shao-Hsuan; Lin, Feng-Huei; Hsu, Tzu-Sheng; Lin, Lih-Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Micron-scale structure biphasic calcium phosphate (BCP) materials have demonstrated promising clinical outcomes in the field of bone tissue repair. However, research on BCP materials at the nanoscale level remains limited. In this study, we synthesize granular-shaped BCP nanomaterials with multiple desirable characteristics, including negatively charged surfaces, noncytotoxicity, and the capability to penetrate cells, using a nanogrinding dispersion process with a polymeric carboxylic acid as the dispersant. Our results reveal that treating human osteoblasts with 0.5 μg/mL BCP nanomaterials results in a marked increase in alkaline phosphatase (ALP) activity and the upregulation of osteogenesis-related genes. Furthermore, these BCP nanomaterials exhibit immunomodulatory properties. Treatment of THP-1-derived macrophages with BCP nanomaterials decreases the expression of various inflammatory genes. BCP nanomaterials also mitigate the elevated inflammatory gene expression and protein production triggered by lipopolysaccharide (LPS) exposure in THP-1-derived macrophages. Notably, we observe that BCP nanomaterials have the capacity to reverse the detrimental effects of LPS-stimulated macrophageconditioned medium on osteoblastic activity and mineralization. These findings underscore the potential utility of BCP nanomaterials in clinical settings for the repair and regeneration of bone tissue. In conclusion, this study highlights the material properties and positive effects of BCP nanomaterials on osteogenesis and immune regulation, opening a promising avenue for further research on inflammatory osteolysis in patients undergoing clinical surgery.